1975
DOI: 10.1146/annurev.ph.37.030175.001545
|View full text |Cite
|
Sign up to set email alerts
|

Defense Mechanisms of the Lungs

Abstract: ·:·1133Nonviable particles enter the atmosphere from forest fires, wind action on dessicated soil, entrainment of sea spray, volcanic debris, and gas phase reactions. Man-made sources account for approximately 185-415 X 106 metric tons per year out of an estimated total of 985-26 15 X 106 metric tons per year and are generated from less than 1% of the earth's surface (6 1, 83, 195). The size of the particle is the single most important feature of an aerosol because it determines the stability of the aerosol. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…Based on the results of this study, the effect of acute CB exposure at 67 wks appeared to be limited to the conducting airways without causing changes in the lung parenchyma. In a review by Cohen and Gold (1975) {Cohen, 1975 #126}, the authors indicated that deposition of particles in upper airways results in constriction without affecting compliance. This concept of particle deposition seems to be consistent with the current results in mice indicating that acute effects of CB exposure were related to changes in the upper airways compared to distal changes in the lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results of this study, the effect of acute CB exposure at 67 wks appeared to be limited to the conducting airways without causing changes in the lung parenchyma. In a review by Cohen and Gold (1975) {Cohen, 1975 #126}, the authors indicated that deposition of particles in upper airways results in constriction without affecting compliance. This concept of particle deposition seems to be consistent with the current results in mice indicating that acute effects of CB exposure were related to changes in the upper airways compared to distal changes in the lung parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Purified diacylphospholipids had no antibacterial activity, however, a lysophospholipid, palmitoyl lysophosphatidylcholine, had many properties resembling the surfactant-containing fraction of lavage, including autolysin-mediated pneumococcal lysis, altered cell membrane permeability, and antibacterial activity against several gram-positive bacteria. INTRODUCTION It is frequently stated that inhaled bacteria are killed by alveolar macrophages (1,2). This view is based (10).…”
mentioning
confidence: 99%
“…38 Various inorganic materials such as beryllium, barium salts, zirconium and silica are localised within tissues, often within macrophages. This eventually results in granulomatous and excessive fibrotic reactions.…”
Section: Removal Of Damaged Cells Debris and Inorganic Materialsmentioning
confidence: 99%